Comparing Foreseeability in Contractual Damages under the CISG, Unidroit Principles and Principles of European Contract Law - QuynhNguyen Thi (Pázmány Law Review, 2025)
In contract law, when one party breaches its contractual obligations, the aggrieved party may claim to recover damages; however, they are not always entitled to the full amount of loss or damages caused. To limit damages in contract disputes, national legal systems and international instruments have introduced foreseeability into the contract language. The aim of this research is to investigate foreseeability as it has been applied under the Vienna Sales Convention (CISG), the UNIDROIT Principles (UPICC) and the Principles of European Contract Law (PECL). In the study, the principle of foreseeability is examined as regulated in these three instruments with a comparison of their similarities and differences. While textual differences between the instruments are minor, challenges remain in interpreting foreseeability rule including its ambiguity and uncertainty. Nonetheless, the broad and flexible approach of foreseeability continues to be effective in the global commercial context.